2021
DOI: 10.1016/j.bja.2020.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Epidural blood patch for post-dural puncture headaches in adult and paediatric patients with malignancies: a review

Abstract: Many anaesthetists are hesitant to perform epidural blood patch in patients with cancer because of the potential risk of seeding the CNS with malignant cells. Recent evidence suggests that anaesthetists may view malignancy as a relative contraindication to epidural blood patch rather than an absolute contraindication. This review article summarises the clinical dilemma, reviews the existing literature, and proposes a treatment algorithm that includes the utilisation of for the management of post-dural puncture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Sealing the site of dural puncture by injection of autologous blood into the epidural space through EBP is usually considered the last resort after the failure of conservative and pharmacological treatments. However, the indications for this technique remain an important concern in certain clinical scenarios such as potential seeding of malignant cells [28] or viral particles [29,30] in the central nervous system as well as the effects of anticoagulants used for the known hypercoagulable state in COVID-19-positive patients [29,30] . Other complications from EBP also included secondary low back pain, lumbar vertebral syndrome, intrathecal blood injection, subacute subdural hematoma, and adhesive arachnoiditis [27,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Sealing the site of dural puncture by injection of autologous blood into the epidural space through EBP is usually considered the last resort after the failure of conservative and pharmacological treatments. However, the indications for this technique remain an important concern in certain clinical scenarios such as potential seeding of malignant cells [28] or viral particles [29,30] in the central nervous system as well as the effects of anticoagulants used for the known hypercoagulable state in COVID-19-positive patients [29,30] . Other complications from EBP also included secondary low back pain, lumbar vertebral syndrome, intrathecal blood injection, subacute subdural hematoma, and adhesive arachnoiditis [27,31] .…”
Section: Discussionmentioning
confidence: 99%
“…In leukemia, the indication for EBP should be determined by the minimal residual disease status of the peripheral blood and the CNS disease. 7 We describe a case of epidural CSF leak with lower limb paralysis after IT, which improved conservatively within 3 weeks without sequelae. This study makes a novel contribution to the literature by revealing the watchful waiting of epidural CSF leak with neurological abnormalities after IT.…”
Section: Epidural Cerebrospinal Fluid Leak With Neurologic Abnormalit...mentioning
confidence: 92%
“…In previous reports of epidural CSF leak due to LP without IT, neurological abnormalities, such as lower-extremity weakness, healed conservatively, without sequelae. [2][3][4] On the other hand, only two patients with epidural CSF leak or subarachnoid cutaneous fistula after IT underwent EBP because their symptoms did not improve within 72 h. 5,6 Although EBP is considered safe and effective in adult patients, 7 Strand et al 9 reported that one out of 19 patients with leukemia or lymphoma who received EBP, developed new CNS involvement. Additionally, LPs for EBP have potential risks with subdural abscesses and septicemia.…”
Section: Epidural Cerebrospinal Fluid Leak With Neurologic Abnormalit...mentioning
confidence: 99%
“…PDPH generally manifests at 3 days up to 2 weeks following lumbar LP with clinical signs and symptoms of frontooccipital non-throbbing postural headache, as it improves when lying flat and worsens in the upright position. 3 The influence of positional changes is one of the most important diagnostic criteria for PDPH. Other symptoms include nausea, vomiting, hearing impairment, photophobia, low back pain, and neck stiffness.…”
Section: Introductionmentioning
confidence: 99%